BUDIDAYA PADI SAWAH ORGANIK UNTUK PEMULIHAN KESEHATAN TANAH DAN PENGURANGAN RESIDU PESTISIDA PADA PRODUK HASIL PERTANIAN - Valentino Valentino; Imam Wahyudi; Irwan Lakani; Sri Anjar Lasmini; Usman Made; Idham Idham (Universitas Indraprasta PGRI, 2022)
The tendency of more intensive use of chemicals in agricultural cultivation activities causes an imbalance of other nutrients and decreases the content of soil organic matter. This causes degradation of soil fertility and residues of active pesticides that threaten the sustainability of farming. The community partnership program (PKM)aimed to provide solutions to problems faced by partners in both the production and management fields by providing counseling, demonstrations and assistance. The method activities is participatory rural appraisal (PRA) in applying appropriate technology and empowerment, with partners in these activities being members of the